On the turn-inducing properties of asparagine: the structuring role of the amide side chain, from isolated model peptides to crystallized proteins. Issue 5 (19th January 2018) - Habka, S.; Sohn, W. Y.; Vaquero-Vara, V.; Géléoc, M.; Tardivel, B.; Brenner, V.; Gloaguen, E.; Mons, M.
Abstract : The anchoring properties of an asparagine (Asn) residue to its local backbone environment in turn model peptides is characterized using gas phase laser spectroscopy and compared to crystallized protein structures. Abstract : Asparagine (Asn) is a powerful turn-inducer residue, with a large propensity to occupy the second position in the central region of β-turns of proteins. The present work aims at investigating the role of a local anchoring between the Asn side chain and the main chain in this remarkable property. For this purpose, the H-bonding patterns of an asparagine residue in an isolated protein chain fragment forming a γ- or a β-turn have been determined using IR/UV double resonance gas phase spectroscopy on laser-desorbed, jet-cooled short models in conjunction with relevant quantum chemistry calculations. These gas phase data provide evidence for an original double anchoring linking the Asn primary amide side chain (SC), which adopts a gauche + rotameric form, to its main chain (MC) local environment. From both IR spectroscopic evidence (H-bond induced red shifts) and quantum chemistry, Asn SC is found to behave as a stronger H-bond acceptor than donor, resulting in stronger MC→SC H-bonds than SC→MC ones. These gas phase structural data, relevant to a hydrophobic environment, have been used as a reference to assess the anchoring taking place in high resolution crystallized proteins of the Protein Data Bank. This approach reveals that, when the SC adopts a gauche + orientation, the stronger MC→SC bonds are preserved in many cases whereas the SC→MC bonds are always disrupted, in qualitative agreement with the gas phase ranking of these interactions. Most interestingly, when Asn occupies the second position of central part of a β-turn ( i.e., the very turn-inducer position), the MC→SC H-bonds are also disrupted and replaced by a water-mediated SC to MC anchoring. Owing to the specific features of the hydrated Asn side chain, we propose that it could be a turn precursor structure, able to facilitate turn formation in the early events of the folding process.